Budaya Organisasi Dan Profesionalisme Perawat Di Rumah Sakit Swasta Di Temanggung - Raharjo Apriyatmoko; Eko Susilo (Jurnal Manajemen Keperawatan, 2014)
Organizational culture is one important aspect in achieving an organization’s objectives, including in influencing professionalism. PKU Muhammadiyah Hospital in Temanggung regional is assumed have strong organizational culture differently in raising the level of professionalism of the nurses. The researcher’s goal is to determine the influence of the strength of cultural organization with professionalism of nurses at PKU Muhammadiyah. The study was conducted by applied cross sectional approach with 55 nurses. The questionnaires were used for data collecting tested by management experts (content validity).The results show that there is a significant positive relation ( r = 0.445 ) between the organizational culture and profesonalism. Based on the research, it is required to develop an organizational and managerial system, from both hospitals and nursing profession in PKU Muhammadiyah hospital in developing a system, therefore the cultural values of the organization that are developed in the hospitals can be strengthened .